Perilaku Religiositas Remaja: Kasus pada Siswa SLTA di Jakarta Selatan, Lebak, dan Sukabumi - Masri Mansoer (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
Declining of adolescent religiosity these days represent the ruination process of a nation. Number of news in mass media about the boisterous of moral decadence phenomenon, badness and mischief done by adolescent do not only show that ruination marking nation happened, but also show off the crisis of character and moral that happened at all nations. This moral decadence, forerunner less function of religion, ruination of family structure, collapse education mission, and develop mint orientation at economic growth, so that alter the value of human life become the items hunter, estate, position, and secularistic.